ANALISIS PENGARUH PROMOSI, INOVASI PRODUK, DAN SALURAN DISTRIBUSI TERHADAP CITRA MEREK SEPATU OLAHRAGA ADIDAS DI KOTA SEMARANG - Laksono, Enggar Bangkit; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2019)
This study aims to analyze whether Promotion, Innovation, and Distribution Channels affect the brand image of Adidas sports shoes. This study uses three independent variables namely Promotion, Innovation, and Distribution Channels and uses one dependent variable, Brand Image. The sample used in this study were 96 consumers of Adidas sport shoes in Semarang City. Data collection methods used were questionnaires distributed with non-probability sampling techniques with the type of purposive sampling. The data analysis technique used is quantitative. The results obtained from this study were obtained a significant T test value, namely for Promotion, Innovation, and Distribution Channels which means that all variables have a positive effect on Brand Image. And the value of the coefficient of determination is 0.530, which means that 53% of Brand Image is influenced by Promotion, Innovation, and Distribution Channels.